Density Indexes in Determining an Urban Sprawl using Remote Sensing and GIS Techniques. - Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Nuraulia, Rusni (2014)
Urban density represents the amount of land occupied by a number of residents and an important factor in understanding how cities function. It is one of the essential components in measuring urban sprawl. The urban density index provides a measure of how much land is consumed per capita for a patch of new development. It is commonly asserted that higher density cities are more sustainable than low density cities because it consumes more land for each resident leaving less of the landscape able to function in other capacities. While some researcher argue that low-density urban area contributed to sprawl, others have counter that higher density results in more negative impact. Characterizing urban sprawl by using density index requires suitable and proper technique. This research attempts to study the measurement of sprawl by using density index with Remote Sensing and Geo-information System (GIS) approach. The SPOT-5 images with 2.5 meters resolution were used and combined with GIS database to analyse the growth of sprawl in Kuala Lumpur metropolitan due to its high-density development. To achieve a better urban development and infrastructure planning in the future, it is crucial for the City Hall to know sprawl phenomenon in Kuala Lumpur, its types, distribution, factors, and the way it is likely to move in the years to come. By using Remote Sensing and GIS, high density area and low density area in Kuala Lumpur can be analysed and compared. The findings show that Kuala Lumpur is a sprawling city. Suitable measures can be adopted by responsible authority to overcome urban sprawl issues in Kuala Lumpur. It is anticipated that this research will provide a new direction in urban sprawl studies and represent a robust analytic approach for characterizing urban development in the city scale at once as well as promoting a city via Remote Sensing and GIS technology.